Histomorphometric evaluation of strontium-containing nanostructured hydroxyapatite as bone substitute in sheep - Callinca Paolla Gomes MACHADO; Suelen Cristina SARTORETTO; Adriana Terezinha Neves Novellino ALVES; Inayá Barbosa Correa LIMA; Alexandre Malta ROSSI; José Mauro GRANJEIRO; Mônica Diuana CALASANS-MAIA (Sociedade Brasileira de Pesquisa Odontológica, 2016)
Abstract The aim of this study is to evaluate the biocompatibility and osteoconductivity in surgical defects of sheep tibias filled with 1% strontium-containing nanostructured hydroxyapatite microspheres (SrHA), stoichiometric hydroxyapatite without strontium microspheres (HA), or blood clots. Santa Ines sheep were subjected to three perforations on the medial side of the left tibia. The biomaterials were characterized by X-ray Diffraction (XRD) and Fourier Transform Infrared (FTIR) before implantation and by X-Ray Microfluorescence (µFRX) and Scanning Electron Microscopy (SEM) after sheep tibias implantation. Surgical defects were filled with blood clots (control), SrHA (Group 1) or HA (Group 2). After 30 days, 5-µm bone blocks were obtained for histological evaluation, and the blocks obtained from 1 animal were embedded in methylmethacrylate for undecalcified sections. Mononuclear inflammatory infiltrate remained mild in all experimental groups. Giant cells were observed surrounding biomaterials particles of both groups and areas of bone formation were detected in close contact with biomaterials. All groups showed newly formed bone from the periphery to the center of the defects, which the control, HA and SrHA presented 36.4% (± 21.8), 31.2% (± 14.7) and 26.2% (± 12.9) of newly formed bone density, respectively, not presenting statistical differences. In addition, the connective tissue density did not show any significant between groups. The SrHA showing a higher volume density of biomaterial (51.2 ± 14.1) present in the defect compared to HA (32.6 ± 8.5) after 30 days (p = 0.03). Microspheres containing 1% SrHA or HA can be considered biocompatible, have osteoconductive properties and may be useful biomaterials for clinical applications.